Biomorphological and useful agronomic traits of the hexaploid winter triticale cultivar ‘Bilinda’ approved for cultivation in the Northwestern Region of the Russian Federation - L. P. Bekish; V. A. Uspenskaja; T. I. Peneva; N. N. Chikida (Труды по прикладной ботанике, генетике и селекции)
A priority of agricultural production for the Northwest of Russia is to develop and introduce winter-hardy and productive cultivars of small grain forage crops, such as winter triticale, capable of producing high yields of grain and green biomass.‘Bilinda’, a new promising tetraploid winter triticale cultivar grown for grain forage, was studied from 2004 through 2019 at Leningrad Research Institute for Agriculture “Belogorka”. The data of the State Variety Trials (2017–2019) were also taken into account. Conventional techniques were used in the experiments, phenological observations, field and laboratory evaluation tests, and statistical data processing. Electrophoresis of gliadin in the grain of cv. ‘Bilinda’ and its registration as a “protein formula” were performed using the technique developed and approbated by the Molecular Biology Dept. of VIR. The hexaploid winter triticale cultivar ‘Kornet’ (k-3636) served as the reference. Cv. ‘Bilinda’ was developed using individual and mass selection of genotypes with recessive control of the ear’s morphological characters, which resulted in producing a homogeneous population with high yield potential and large plump grains. On average across the testing period, cv. ‘Bilinda’ significantly exceeded the reference ‘Kornet’ in grain yield (+1.04 t/ha), number of grains per ear (+32.3 pcs), and 1000 grain weight (+7.7 g), and in addition demonstrated higher winter hardiness than the reference (up to 98%). Under epiphytotic incidence of Septoria leaf blotch, the tested cultivar manifested a high level of resistance (scoring 7–9 points). ‘Bilinda’ is among high-yielding cultivars resistant to most leaf diseases. In 2020, this cultivar was approved for cultivation in the Northwestern Region (2) of Russia. Applying the method of variety identification based on the electrophoretic spectra of gliadin, a storage protein in grain, a protein “passport” was produced to ensure monitoring of the cultivar’s integrity and authenticity.